2015
DOI: 10.4103/0975-7406.155963
|View full text |Cite
|
Sign up to set email alerts
|

Role of dietary habits and diet in caries occurrence and severity among urban adolescent school children

Abstract: To identify the role of dietary habits (type of diet, skipping meals, snacking in-between meals and frequency of visits to fast food restaurants) in caries occurrence and severity. To explore the correlation between frequency of intake of selected foods and dental caries. A cross-sectional study was carried out on adolescent children (n = 916) of age 13-19, following a two-stage random sampling technique. Data were collected using a pretested questionnaire. Questionnaire included demographic details, dietary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 12 publications
6
42
2
6
Order By: Relevance
“…Logistic regression analysis revealed that overweight or obese adolescents are more likely to have serious risk behavior for eating disorders, corroborating previous findings [ 30 , 31 ]. Thus, it was observed that higher BMI leads to greater dissatisfaction with appearance and increased prevalence of eating disorders [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Logistic regression analysis revealed that overweight or obese adolescents are more likely to have serious risk behavior for eating disorders, corroborating previous findings [ 30 , 31 ]. Thus, it was observed that higher BMI leads to greater dissatisfaction with appearance and increased prevalence of eating disorders [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…The self-administered questionnaire combined from previously reported researchers [ 12 ] [ 13 ] gathering information about the close-ended questions into four parts as demographic characteristics (age, gender, educational level and income of the parents) followed by 18 questions related to diet (6 question), dietary habits (6 question) and hygiene habits (6 questions).…”
Section: Methodsmentioning
confidence: 99%
“…But several procedural imperfections built in these studies make it hard to confirm a convinced association between dietary habits and dental caries (Screenby, 1975; Newbrun, 1982) [ 11 ]. But its role cannot be taken trivially from the recent studies [ 12 ] [ 13 ] where it is proved that dietary habits take a very important role.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of different study sex, age, dietary habits,education, and oral hygiene status are associated with increased prevalence of dental caries (25,27,31). Likewise, the growing consumption of sugared foods in the developing world, poor tooth brushing habits, poor oral hygiene and low level of awareness about dental caries are some of the factors that increased the levels of dental decay (23,(32)(33)(34). On the contrary frequent tooth brushing was a lower chance of having decayed (5).…”
Section: Introductionmentioning
confidence: 99%